Porcine non-conventional B-1-like cells are a potent source of Streptococcus suis-binding IgM - Seidel, Anne-Marie; Kauffold, Johannes; Protschka, Martina; Baums, Christoph G.; Alber, Gottfried; Eschke, Maria (Frontiers in Immunology, 2024)
IntroductionStreptococcus suis serotype (cps) 2 is an important bacterial pathogen in piglet nurseries and an emerging zoonotic agent without effective vaccines available. Immunoglobulin (Ig)M plays an essential role in host defense against S. suis. In mice, non-conventional B-1 cells are a major source of protective IgM against encapsulated bacterial pathogens, such as S. pneumoniae. Two IgM+CD21− B-1-like cell subpopulations, distinguishable by CD11R1 expression, were described in pigs, but their properties and functions are poorly understood. This study aimed at a first characterization of the porcine early IgM B cell response against S. suis cps 2.MethodsWe analyzed the same healthy pigs, naturally colonized by different S. suis serotypes, including cps 2, at four and eight weeks of age serologically and determined the frequency of different peripheral B cell subpopulations by flow cytometry. Furthermore, we isolated conventional IgM+CD21+ B-2 cells as well as non-conventional B-1-like cell subpopulations from peripheral blood of eight-weeks-old pigs to evaluate their potential of IgM secretion in response to innate and adaptive stimuli in vitro.ResultsBetween the fourth and eighth week of life, a characteristic increase of S. suis cps 2-binding serum IgM antibodies, restricting bacterial growth, was observed. Moreover, we show for the first time that the significant increase of anti-S. suis serum IgM is associated with a relative increase of peripheral non-conventional IgM+CD21− B-1-like cells in vivo, particularly of the IgM+CD21− CD11R1− subpopulation. Noteworthy, sorted IgM+CD21− CD11R1− B-1-like cells from eight-weeks-old pigs spontaneously secreted IgM in vitro. In addition, both non-conventional IgM+CD21− B cell subpopulations, in contrast to conventional IgM+CD21+ B-2 cells, produced anti-S. suis IgM upon toll-like receptor (TLR) stimulation underlining their innate-like characteristics. We furthermore observed that both B-1-like subpopulations secrete S. suis cps 2-binding IgM upon stimulation with T cell-associated factors with highest amounts in IgM+CD21−CD11R1− B-1-like cells even exceeding anti-S. suis IgM levels produced by B-2 cells.ConclusionPorcine non-conventional B-1-like cells are a potent source of S. suis-binding IgM indicating a role in immunity during a critical phase of piglet rearing.